Synthesis, characterization and HDS activity of Co catalysts supported on natural, acid, Al- and Fe-pillared smectite clays - González, Eduardo; Troconis, María; Solano, Roger; Sánchez, Jorge; Moronta, Alexander (Ciencia, 1970)
Two montmorillonites, SWy-2 (Wyoming, USA) and STx-1 (Texas, USA) (henceforth referenced as SW and ST) were acid activated, pillared with aluminum or iron and then impregnated with Co. Catalysts using the raw clays were also prepared. The synthesized catalysts were characterized by X-ray diffraction, thermal analysis, surface area, acidity determinations and temperature programmed reduction. The catalytic activity was measured using the hydrodesulfurization of thiophene at 350°C. Acid and pillaring treatments increased the surface area, porosity and acidity. In all catalysts, microporosity and mesoporosity were observed. The surface area and porosity of the catalysts were not affected by Co incorporation, however the acidity decreased. The reduction profiles showed the formation of several surface species of cobalt with aluminum and iron in both Al- and Fe-pillared clays. The activity for the hydrodesulfurization of thiophene depended on the chemical properties and textural characteristics of the support. The most active Co catalysts were those supported on acid activated clays (11 and 45% for Co/HSW and Co/HST), followed by those supported on Al-pillared clays (7 and 15% for Co/AlSW and Co/AlST) and Fe-pillared clays (2 and 17% for Co/FeSW and Co/FeST) and on the raw clays, which showed the lowest conversions (2 and 6% for Co/SW and Co/ST).